1984
DOI: 10.1152/ajpendo.1984.246.1.e62
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional influences on lipogenesis and thermogenesis after a carbohydrate meal

Abstract: In vivo lipogenesis and thermogenesis were studied for 24 h after ingestion of 500 g of carbohydrate (CHO) in subjects who had consumed either a high-fat, a mixed, or a high-CHO diet during the 3-6 days preceding the test. CHO oxidation and conversion to fat was significantly less in the high-fat diet group (222 +/- 5 g) than in the mixed (300 +/- 13 g) or high-CHO diet (331 +/- 7 g) groups, resulting in a greater glycogen storage in the high-fat (278 +/- 6 g) than in the other two groups (197 +/- 11 and 170 +… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
117
1

Year Published

1988
1988
2004
2004

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(126 citation statements)
references
References 20 publications
8
117
1
Order By: Relevance
“…The logical question related to this issue is how the direct energy 'cost of oxidation' of a substrateFa process that aims at providing ATP's rather than consuming itFcould be greater than the cost of transformation of the same substrate into another substrate. Another issue which contradicts Acheson's assumption is that the magnitude of overall DNL (estimated by indirect calorimetry) has been found to be positively and highly significantly correlated (r ¼ 0.71) to the thermic effect of food in a situation in which there is no net fat storage due to DNL over 24 h. 7 The slope of the regression line suggests that a net lipogenesis of 10 g/day increases the absolute thermogenesis by 70%.…”
Section: Introductionmentioning
confidence: 93%
“…The logical question related to this issue is how the direct energy 'cost of oxidation' of a substrateFa process that aims at providing ATP's rather than consuming itFcould be greater than the cost of transformation of the same substrate into another substrate. Another issue which contradicts Acheson's assumption is that the magnitude of overall DNL (estimated by indirect calorimetry) has been found to be positively and highly significantly correlated (r ¼ 0.71) to the thermic effect of food in a situation in which there is no net fat storage due to DNL over 24 h. 7 The slope of the regression line suggests that a net lipogenesis of 10 g/day increases the absolute thermogenesis by 70%.…”
Section: Introductionmentioning
confidence: 93%
“…8 This disequilibrium has been demonstrated in a number of experimental studies. 9,10 In contrast, observations from some crosssectional studies have shown an inverse association between energy intake and obesity. 11,12 One explanation for the inverse association is an underestimation of food intake by obese individuals.…”
Section: Introductionmentioning
confidence: 93%
“…A number of studies (Acheson et al, 1982(Acheson et al, , 1984 have con®rmed that a single meal containing large amounts of CHO energy (up to 500 g CHO) in previously weight stable subjects does not cause NP RQ to rise above 1.0. This has been interpreted as evidence against a quantitatively important role for DNL in the dayto-day storage of surplus CHO energy; also, storage as glycogen was concluded to represent the fate of excess dietary CHO.…”
Section: Indirect Calorimetry To Measure Net Dnl In the Whole Bodymentioning
confidence: 99%